Wire Arc Additive Manufacturing for Lightweight Material Applications: A Systematic Literature Review - Agus Widyianto; Heri Wibowo; Riswan Dwi Djatmiko; Atik Setyani (Universitas Negeri Yogyakarta, 2026)
Wire arc additive manufacturing (WAAM) is increasingly used to fabricate large lightweight metal components because it combines wire feedstock, arc-based heat sources, high deposition rate, and high material utilization. This systematic literature review evaluates recent progress in WAAM for aluminum, titanium, and magnesium alloys, with emphasis on process parameters, microstructure, mechanical properties, defects, and industrial applications. The review followed the PRISMA 2020 framework and searched three academic search platforms using six structured queries covering WAAM, lightweight alloys, process parameters, mechanical behavior, microstructure, defects, and applications. From 1,052 records, 305 duplicates were removed, 747 records were screened, 270 papers were assessed in full text, and 265 studies were included in the evidence synthesis. Aluminum alloys were the most frequently reported material system, particularly Al-Mg, Al-Si, Al-Cu, and Al-Zn-Mg-Cu alloys, followed by Ti-6Al-4V and magnesium alloys such as AZ31, AZ91, and WE43. The synthesis shows that heat input, wire feed speed, travel speed, interpass temperature, shielding gas, and deposition strategy strongly control bead geometry, grain morphology, porosity, residual stress, and anisotropy. Cold metal transfer and pulsed arc variants generally improve process stability for aluminum alloys. At the same time, titanium and magnesium systems require stricter oxidation and thermal-cycle control. Optimized WAAM parts can approach wrought-material properties. However, porosity, hot cracking, surface waviness, distortion, and limited in-situ quality assurance remain barriers to wider certification. Future work should prioritize closed-loop monitoring, WAAM-specific alloy design, hybrid post-processing, fatigue qualification, and life-cycle assessment for large-scale lightweight structures. This review provides a concise evidence map to support parameter selection and research planning for WAAM-based lightweight components.